Shear Plus Squeeze Mode Based Magneto-Rheological Fluid Brake - Patil, Sonal V.; Kumbhar, Bhau K. (Asian Review of Mechanical Engineering, 2015)
Nowadays, magneto rheological fluid technology is growing rapidly to satisfy the different application demands. However, yield stress produced by the MR fluid limits its use option only several applications. Yield stress produced by a typical MR fluid is only 70 -90 kPa. Hence, while exploring the possibility of this fluid to be used in MR brake, it cannot attain required braking torque. Thus, if a conventional shear mode of this MR brake is combined with the simultaneous compression mode, then the typical MR fluid can attain a yield stress of about 800-900 kPa which will satisfy the braking torque requirements. During this review, the theoretical research has been carried out about the shear plus squeeze mode based MR brake to satisfy automotive brake application requirements.